Gelation of an alginate film via spraying of calcium chloride droplets. (29th June 2018) - Lee, Boon-Beng; Bhandari, Bhesh R.; Howes, Tony
Graphical abstract: Highlights: First study on external gelation of alginate solution with a limited amount of CaCl2 . An alginate film was gelled by spraying with a limited supply of CaCl2 . 'Gentle' external gelation of Ca-alginate gel without a curing bath. One-dimensional diffusion–reaction model depicts the concentration-distance profiles. The measured and predicted collection efficiency and film gelation were comparable. Abstract: External gelation process of Ca-alginate gel with a controlled supply of CaCl2 to alginate solution was experimentally and numerically investigated. A single Na-alginate solution film was prepared and suspended in a closed chamber of CaCl2 spray droplets. The collected mass of CaCl2 by the film increases as the spraying time increases. The collection efficiency ( E ) between the film and CaCl2 droplets was averagely 0.0015. The degree of gelation ( P ) of the film was found to be alginate and CaCl2 solution concentration dependent. The experimental results of the mass of CaCl2 droplets collected by the film and the E were in good agreement with the numerical results. The concentration-distance profiles of Ca 2+ cation, alginate, and Ca-alginate gel in the film were determined using the one-dimensional diffusion–reaction model. The model is useful to determine the P of the Ca-alginate gel film produced using a limited supply of CaCl2 .